Chronic Obstructive Pulmonary Disease and Risk of Cutaneous T-cell Lymphoma: A Danish Population-based Cohort Study - Sissel B.T. Soerensen; Dávid Nagy; Niels Ødum; Lars Iversen; Lise M. Lindahl (Medical Journals Sweden, 2023)
Abstract is missing (Short communication)